2022
DOI: 10.3390/genes13111956
|View full text |Cite
|
Sign up to set email alerts
|

Functional Study on Cytochrome P450 in Response to L(−)-Carvone Stress in Bursaphelenchus xylophilus

Abstract: Bursaphelenchus xylophilus (PWN) causes pine wilt disease (PWD), which is one of the most devastating pine diseases worldwide. Cytochrome P450 (CYP) catalyzes the biosynthetic metabolism of terpenoids and plays an important role in the modification of secondary metabolites in all living organisms. We investigated the molecular characteristics and biological functions of Bx-cyp29A3 in B. xylophilus. The bioinformatics analysis results indicated that Bx-cyp29A3 has a transmembrane domain and could dock with L(−)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…It has been reported that these xenobiotic metabolites can induce the expression of the detoxification genes, including the CYP genes, in PPNs. For example, in B. xylophilushave, CYP29A3 was upregulated by L(-)-carvone, a plant metabolite (Chen et al, 2022). Zhang et al (2020) reported that the gene expansion of CYP family is linked to the detoxification of terpenes, which are main defence chemicals in pine wood against parasites.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that these xenobiotic metabolites can induce the expression of the detoxification genes, including the CYP genes, in PPNs. For example, in B. xylophilushave, CYP29A3 was upregulated by L(-)-carvone, a plant metabolite (Chen et al, 2022). Zhang et al (2020) reported that the gene expansion of CYP family is linked to the detoxification of terpenes, which are main defence chemicals in pine wood against parasites.…”
Section: Discussionmentioning
confidence: 99%